STRATEGI PENGEMBANGAN POTENSI PARIWISATA KABUPATEN SOPPENG - Ika Mahkota Putri (STIE AMKOP, 2020)
This study aims to determine (1) internal and external conditions and (2) Formulate a strategy for developing tourism potential in Soppeng district. This research was conducted in Regency. The method used in this study was a descriptive method with a qualitative approach. The informant in this study was the official policy maker in and relating to the development of tourism potential for for tourism development. Data collection techniques used in this study were observation, interviews and documentary studies. The results of this study indicate that the formulation of a strategy to develop tourism potential and a combination of external and internal factors is (1) utilizing an adequate tourism budget for developing all existing potentials, (2) improving the quality of theapparatus, specifically in the field of tourism in order to overcome tourism problems (3) increasing efforts to deal with environmental damage (4) increasing tourism promotion efforts. Keywords : Strategy, Development, Potential.